Nanomedicine in Cancer Therapy: Opportunities, Challenges, and Future Directions - Felipe Souza; Bruna Costa; Rafaela Lima; Dito Anurogo (Yayasan Adra Karima Hubbi, 2025)
Cancer remains one of the leading causes of mortality worldwide, demanding innovative therapeutic strategies that enhance efficacy while minimizing systemic toxicity. Nanomedicine, integrating nanotechnology with pharmacology, offers transformative potential for precision drug delivery, early diagnosis, and targeted therapy in oncology. This study aims to explore the opportunities, challenges, and future directions of nanomedicine in cancer treatment through a comprehensive analysis of recent scientific advancements and clinical trials. A systematic review method was employed, synthesizing data from 130 peer-reviewed studies published between 2015 and 2024. The findings reveal significant improvements in drug bioavailability, tumor-specific accumulation, and controlled release using nanoparticle-based platforms such as liposomes, dendrimers, and polymeric micelles. However, translational barriers persist, including biocompatibility issues, large-scale manufacturing limitations, and regulatory uncertainty. The study concludes that while nanomedicine has demonstrated remarkable therapeutic potential, its clinical integration requires multidisciplinary collaboration and standardized evaluation frameworks to ensure safety, scalability, and cost effectiveness. The insights contribute to a forward-looking perspective on developing next generation nanotherapeutics capable of reshaping cancer care through personalized, minimally invasive, and efficient interventions.